Medullary thyroid carcinoma: biology - management - treatment - Raue, Friedhelm (Recent Results in Cancer Research, 2015)
This book offers a comprehensive overview of medullary thyroid carcinoma, both in the more common sporadic form and in the familial form, multiple endocrine neoplasia (MEN) types 2A and 2B. The coverage includes, but is not limited to, molecular biology and genetics, pathology, clinical presentation, imaging techniques, surgical treatment, and follow-up. The role of calcitonin as a highly sensitive and specific tumor marker for the screening, diagnosis, and follow-up of MTC and metastatic disease is described, and the significance of other tumor markers is also considered. With regard to treatment, the use of thyroidectomy is fully discussed, including in children carrying the mutations in the RET proto-oncogene considered causative for MEN 2. Additionally, the value of tyrosine kinase inhibitors as the most effective treatment modality in patients with a large tumor burden or rapid tumor growth, or both, is explained. Medullary Thyroid Carcinoma and Multiple Endocrine Neoplasia Type 2 will be an ideal source of up-to-date information for a wide range of practitioners, including endocrinologists, oncologists, internal medicine specialists, geneticists, and nuclear medicine physicians